KORELASI JUMLAH BATANG ROKOK DENGAN KADAR CO PADA REMAJA PEROKOK DI SMK KOTA JAMBI - Miko Eka Putri (Universitas Baiturrahim, 2018)
Cigarettes are very dangerous for health. The Global Adults Tobacco Survey (GATS) survey estimated that as many as 7.9 billion adults became active smokers and about 3.5 billion people were exposed to cigarette smoke at work. Indonesia ranks 4th out of 10 countries with a population of smokers (4%) after China (38%), Russia (7%) and the United States (5%) (Ministry of Health, 2012). Every cigarette smoked contains a lot of toxic substances, especially carbon monoxide (CO) which can damage the sympathetic nervous system and hemoglobin desaturation.This study aims to see the effect of the number of cigarettes with CO levels in adolescent smokers in vocational schools. This research is a quantitative research with cross-sectional design. The sample in this study amounted to 20 people in which the sampling technique used was purposive sampling. This study was conducted on July 2018 in SMK in the city of Jambi. Analysis using the Wilcoxon test.The results showed that the average number of cigarettes smoked by teenagers per day was 3.2 cigarettes, and the average CO level was 10.1ppm. The results of the analysis with Wilcoxon test showed that there was an effect of the number of cigarettes on CO levels with a p value of 0,000, meaning that there was a relationship between the number of cigarettes and CO levels in adolescent smokers in SMKs.The results of this study are expected to be a reference for teenagers to know the content of cigarettes and their dangers so that they can stop smoking behavior.